MANAGEMENT TECHNOLOGY OF PROFESSIONAL DEVELOPMENT OF STAFF IN MEDICAL ORGANIZA TIONS - I. A. Revskaia (Исследования и практика в медицине)
The article analyzes the mechanisms and technology management personnel professionalization of medical organizations. The question is now becoming even more relevant within the health care sector optimization, the main purpose of which is claimed to improve the quality of health care by improving the efficiency of health care organizations and their personnel, including the availability of physicians and medical staff, their skills and professionalism. The problems of improving the technology of postgraduate education of doctors examined.